Palliative Care for Chronic Renal Failure Patients: Issues and Recommendations for Development - Nilmanat, kittikorn; Thasaneesuwan, Samonnan; Tinkaew, Phenpitcha (Journal of Thailand Nursing and Midwifery Council, 2021)
A primary goal of palliative care for chronic renal failure patients is to promote their and their families’ quality of life. Such palliative care should cover all the relevant stages, from the diagnosis, to the treatment, to the end-stage care, and to family care after the patient’s death. Major principles of palliative care for chronic renal failure patients consist of 1) identifying the patients in need of palliative care; 2) symptomatic assessment and management; and 3) mutual decision making and advance care planning. Directly responsible for providing palliative care, nurses play a signifcant role in educating and providing information for the patients, giving holistic care to the patients and their families, collaborating with multidisciplinary teams, performing continuous self-development, and upholding the professional ethics. Recommendations for development include integration of palliative care with the early stage of renal diagnosis, development of palliative care teams’ knowledge and skills, improvement of the organisation’s ethical system and mechanisms, and development of research studies that meet accepted standards.